PENGARUH PENERAPAN ATURAN ETIKA, PENGALAMAN DAN SKEPTISME PROFESIONAL AUDITOR TERHADAP PENDETEKSIAN KECURANGAN - Helmiati, Helmiati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The purpose of the research study was to aim empirical evidence in analyze the effect of the application of the rules of ethics, experience and professional skepticism auditor's fraud detection and analyze the most dominant variables between the application of the rules of ethics, experience and professional skepticism auditors that influence fraud detection.The population in this study is the KAP (Public Accounting Firm) located in Java and Sumatra by using Convenience Sampling samples were included in the Non-Probability Sampling. The data used is primary data collection method of data using questionnaires. Data analysis method used is multiple regression (Multiple Regression) with SPSS version 21.0.The results of this study indicate that the increase in the application of ethics rules will provide an increase in fraud detection with 2,349 t greater than t table 1.684 and 0.024 significant. Significantly affect fraud detection experience with the t value 2,334, t table 1.684, 0.024 significant. Professional skepticism proved to significantly affect the detection of fraud with 4,230 t, 1,684 t table significantly with 0,000.